Liquid space : science fiction film and television in the digital age - Redmond, Sean (London: I B Tauris & Co Ltd., 2017)
In this remarkable and original book, Sean Redmond examines the issues and themes that are repeatedly found across a range of contemporary science fiction films and television programmes. He argues that they reveal the profound effects the digital age has had on our social lives. Through narratives that feature the 'post-human', genetic engineering and cloning, surveillance and data mining, space and time travel, artificial intelligence, online dating cultures and visions of catastrophe, they portray a world in which the material, and the stable, are being lost to the ever-more volatile and ephemeral idea of 'liquid space'. Redmond examines a wide selection of popular films and TV series such as Gravity, Under the Skin, The Lobster, Children of Men and Doctor Who, to locate how traditional values are being erased in favour of a new liquid modernity. Drawing on an eclectic range of approaches from phenomenology to critical race theory, and from close textual analysis to the revelations of eye-tracking technology, this book is an illuminating account of the digital age through the lens of science fiction.
Includes bibliographical references (pages 182-190) and index.
Keywords: Science fiction films; Digital cinematography; Performing Arts; Digital cinematography; Science fiction films; Performing Arts